2023
DOI: 10.1021/acs.jmedchem.3c00600
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Potent and Selective Tyrosine Kinase 2 Inhibitor: TAK-279

Abstract: TYK2 is a key mediator of IL12, IL23, and type I interferon signaling, and these cytokines have been implicated in the pathogenesis of multiple inflammatory and autoimmune diseases such as psoriasis, rheumatoid arthritis, lupus, and inflammatory bowel diseases. Supported by compelling data from human genome-wide association studies and clinical results, TYK2 inhibition through small molecules is an attractive therapeutic strategy to treat these diseases. Herein, we report the discovery of a series of highly se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Fragment optimization appears well placed to make use of physics-based computational methods, such as relative and absolute free energy perturbation (FEP), particularly when allied with experimentally derived structural information. These techniques have been used successfully in later-stage hit-to-lead and lead optimization programs; , however, challenges persist with fragments. Binding mode preservation for fragment-sized compounds during molecular dynamic simulations is not guaranteed, and the limited number of known perturbations for novel fragment hits makes predicting the affinity of new designs challenging.…”
Section: Resultsmentioning
confidence: 99%
“…Fragment optimization appears well placed to make use of physics-based computational methods, such as relative and absolute free energy perturbation (FEP), particularly when allied with experimentally derived structural information. These techniques have been used successfully in later-stage hit-to-lead and lead optimization programs; , however, challenges persist with fragments. Binding mode preservation for fragment-sized compounds during molecular dynamic simulations is not guaranteed, and the limited number of known perturbations for novel fragment hits makes predicting the affinity of new designs challenging.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, potency of all compounds decreased in whole blood assays compared with PBMC. This is likely due to the absence of serum in the PBMC assays that delivers free fraction activity, while in whole blood, part of the molecules are trapped by plasma protein as frequently documented. , …”
Section: Resultsmentioning
confidence: 99%
“…The absence of a dose–response relationship is likely due to the involvement of other pathways not impacted by TYK2 inhibition, and to the fact that mass balance studies in mice showed that compound 9 was highly concentrated in the skin (data not shown), suggesting that despite unfavorable PK, it displayed a strong effect in this psoriasis-like model. In addition, it is noteworthy that Leit et al (2023) observed the same partial effects with the TYK2 inhibitor TAK-279, while this compound is more potent than compound 9 and displayed more favorable PK. Other compounds from the same series also gave a partial effect, strongly suggesting that in this model TYK2 inhibitors may not be able to fully counteract all the effects of IL-23.…”
Section: Resultsmentioning
confidence: 99%
“…There are currently no available data on BMS-986322 in patients with psoriasis. TAK-279 (formerly, NDI-034858) is an allosteric TYK2 inhibitor developed by Takeda Therapeutics [73][74][75][76]. In preclinical trials, TAK-279 was 13.0 × 10 4 times more selective for the TYK2-JH2 domain than deucravacitinib, owing to a single amino acid difference in its allosteric binding pocket that prevents binding to JAK1 [74,75].…”
Section: Janus Kinase Inhibitorsmentioning
confidence: 99%